Le Japon, sa politique de défense et l'avenir de son alliance avec les États-Unis - Macleod, Alex (Études internationales, 1992)
The disintegration of the Soviet Union and the Gulf War have forced Japan to question its defence policy. In the past this policy has been firmly based on a purely defensive posture which relied totally on Japan's alliance with the United States. Because the Cold War dragged on in East Asia for much longer than in Europe, Japan could carry on the same defence policy as before. Japanese defence planners found it convenient to emphasize the « Soviet threat » as a way to maintain annual increases in the military budget, and refusing to normalize their relations with the Soviets, until the question of the Northern Territories had been settled. They can no longer ignore the various signs of détente in East Asia. Yet they have had limited effects on Japan's defence policy. The Americans have called on Japan to play a role more commensurate with its economic power but want to avoid any hint of an autonomous Japanese defence policy. They pressured Japan into playing a more active part in the Gulf crisis and the ensuing war, but the government failed to muster sufficient support, at home and amongst the other countries of East Asia, for any role for its military outside Japan, even in a non combat capacity.So Japan has sought other regional and global security policies to compensate for this handicap and has met with mixed success. The recent failure to pass legislation allowing its Self-defence Forces to participate in UN peacekeeping operations has seriously jeopardized Japan 's search for a more active role in regional affairs. But will the Japanese continue for much longer to play a second role in the United States' System of bilateral alliances in the Asia-Pacific region which that country can afford less and less ? This is the real dilemma of Japanese defence policy : it can neither remain as it is nor can it easily change direction.